MURABAHAH FINANCING MECHANISM IN SHARIA CONSUMER COOPERATIVE MITRA NIAGA SEJAHTERA LAMBARO ACEH BESAR, INDONESIA - Mubarrak, Husni; Eriyanti, Nahara; Salsabilla, Tiara (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2023)
One of the financial institutions that contribute effectively to channeling business capital financing is the Sharia Consumer Cooperative Mitra Niaga Sejahtera located in Lambaro Aceh Besar. This institution is supervised by the Sharia Supervisory Board which is tasked with overseeing the operations and practices of LKS in order to adhere to sharia principles. This research examines murabahah financing and looks at the extent of the supervision of the Sharia Supervisory Board at the Mitra Niaga Sejahtera Sharia Consumer Cooperative. So that it raises questions about the murabahah financing mechanism based on the DSN MUI Fatwa Review. In this study the authors used a type of qualitative research and produced data in the form of descriptive analysis. Data collection techniques using interview techniques in the field and documentation. The results of the research obtained that the initial mechanism to become a member / prospective member of murabahah financing is by submitting application for murabahah business capital financing with predetermined conditions, ensuring that murabahah financing is on target, checking the pillars such as contracts, parties to the transaction, objects, objectives and benefits of the financing.